PENGELOLAAN ANGGARAN PENELI TIAN & INOVASI PRODUK DI PT UNILEVER INDONESIA TBK - Andi Asti Handayani; Tuti Supatminingsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine budget management in research and product development activities at PT Unilever Indonesia Tbk. In the Fast-Moving Consumer Goods (FMCG) sector, innovation plays a crucial role in maintaining competitiveness. However, the lack of transparency in the allocation and reporting of R&D budgets is a major challenge. This study employed a descriptive qualitative method with a literature review approach, drawing on secondary data sources, such as academic journals, books, and official reports from Unilever. Budget preparation was conducted using simulations based on the common product innovation stages in the FMCG industry, from market research to product promotion. The findings indicate that budget allocations for each phase need to be designed with flexibility and strategy to adapt to operational changes and innovation needs. Furthermore, it is crucial to integrate information systems and managerial methods that increase the efficiency of R&D funds.